The Effect of Normobaric Hypoxic Confinement on Metabolism, Gut Hormones, and Body Composition - Mekjavic, Igor B.; Amon, Mojca; Kölegård, Roger; Kounalakis, Stylianos N.; Simpson, Liz; Eiken, Ola; Keramidas, Michail E.; Macdonald, Ian A. (Frontiers in Physiology, 2016)
To assess the effect of normobaric hypoxia on metabolism, gut hormones and body composition, eleven normal weight, aerobically trained ( O2peak: 60.6±9.5 ml·kg-1·min-1) men (73.0±7.7 kg; 23.7±4.0 yrs, BMI 22.2±2.4 kg·m-2) were confined to a normobaric (altitude⋍940m) normoxic (NORMOXIA; PIO2⋍133.2 mmHg) or normobaric hypoxic (HYPOXIA; PIO was reduced from 105.6 to 97.7 mmHg over 10 days) environment for 10 days in a randomized cross-over design. The wash-out period between confinements was 3 weeks. During each 10-day period, subjects avoided strenuous physical activity and were under continuous nutritional control. Before, and at the end of each exposure, subjects completed a meal tolerance test, during which blood glucose, insulin, GLP-1, ghrelin, peptide-YY, adrenaline, noradrenaline, leptin, and gastro-intestinal blood flow and appetite sensations were measured. There was no significant change in body weight in either of the confinements (NORMOXIA: -0.7±0.2 kg; HYPOXIA: -0.9±0.2 kg), but a significant increase in fat mass in NORMOXIA (0.23±0.45 kg), but not in HYPOXIA (0.08±0.08 kg). HYPOXIA confinement increased fasting noradrenaline and decreased energy intake, the latter most likely associated with increased fasting leptin. The majority of all other measured variables/responses were similar in NORMOXIA and HYPOXIA. To conclude, normobaric hypoxic confinement without exercise training results in negative energy balance due to primarily reduced energy intake.